A powerful affinity in on-going singular(s) process. Sharing artistic practices in training teachers. - Luc Dall'Armellina; Samira Jamouchi; Kerttuli Saajoranta (European Teacher Education Network, 2022)
In this article, we question and reflect on our collaborative work and research throughout our participation at several European Teacher Education Network (ETEN) conferences. We present four workshops we designed and conducted in Setubal (PT), Rotterdam (NL), Vic (SP) and online (DK). Our experience shows that, far from being a concept reserved only for the private or intimate sphere since the first philosophers, friendship encompasses mutual respect, allowing for creative and fruitful cooperation in arts and education and in formal or informal contexts. We also address singular processes in our workshops using Atkinson's concepts of 'not-know' and 'subjects-yet-to-come'.